Combined proteomics and CRISPR-Cas9 screens in PDX identify ADAM10 as essential for leukemia in vivo - Bahrami, Ehsan; Schmid, Jan Philipp; Jurinovic, Vindi; Becker, Martin; Wirth, Anna-Katharina; Ludwig, Romina; Kreissig, Sophie; Duque Angel, Tania Vanessa; Amend, Diana; Hunt, Katharina; Öllinger, Rupert; Rad, Roland; et al. (Molecular cancer, 2023)
Acute leukemias represent deadly malignancies that require better treatment. As a challenge, treatment is counteracted by a microenvironment protecting dormant leukemia stem cells.